Evaluation of Resting Tongue Position in Partially Edentulous and Completely Edentulous Patients - Bhusal, Dinesh Sharma; Shrestha, Bebina (Journal of BP Koirala Institute of Health Sciences, 2020)
Introduction: Resting tongue position is of crucial importance in the stability and retention of complete denture, particularly of the mandible. The retracted position of the tongue has been found to be higher in edentulous subjects when compared to dentate subjects and highest in completely edentulous individuals. Objectives: To evaluate the resting tongue position in completely edentulous as well as partially edentulous patients. Methods: 50 edentulous and 50 partially edentulous (mandible) subjects were taken. The edentulous group was divided into two groups according to the duration of edentulousness. Group A: Recently extracted edentulous subjects (< 1 year), Group B: Long term edentulous subjects (> 1 years). The partially edentulous group was divided into 4 groups according to Kennedy classification. The resting tongue positions of all the individuals were determined. The data was analyzed using SPSS statistical tests like mean, standard deviation, proportion, Chi-square test and Independent T-test. Results: In complete edentulous group, the abnormal upper was the most frequent (38%). In partial edentulous group, the normal lower was the most frequently observed tongue position with 34%. The abnormal tongue position was found in 68% and 40% in completely edentulous and partially edentulous subjects respectively. Conclusion: Retracted resting tongue position is found to be higher in completely edentulous subjects than partially edentulous ones.